Occupational Interest Patterns and Personality Styles of Freshman Student-Athletes - Denson, Eric L.; Jordan, Janice M.; Green, Kelly E.; Harris, Jennifer A. (My University, 1993)
The existence and relationship of common personality styles and occupational orientations were explored. The study considered Holand's (1973) vocational theory and Strack's (1991) eight basic personality types. Student-athletes (n=36) and non-athletes (n=17) enrolled in a freshman seminar for physical education majors (males = 63%) completed the Personality Adjective Check List (Straclk, 1991) and the Strong Interest Inventory (Hansen & Campbell, 1985). The results suggest that student-athletes and non-athletes differ on several personality and occupacional variables and that personality sryle has an important relationship to occupational orientation and interests. A specific profile for athletes based on personality and vocational type did not emerge. Implications for athletic counseling professionals were discussed.
Keywords: career development; identity